The Non-binary gender as a deconstructed way of interpreting the world - Medina Altamiranda, Said Josue (Disertaciones, 2022)
This article presents theoretical resources that show how non-binary gender has been stigmatized, invisibilized and unrecognized within contemporary Western society. From the language in which we are immersed, patriarchal logic has discriminated against those who do not identify with the hegemonic genders, male-female, which represent two unique ways of seeing the world. Gender defines a way of interpreting the world, therefore, non-binary gender also has this quality. Dialoguing with different genders, including dissidents, will allow us to deconstruct the concepts we have around sex, gender identity, gender expression and sexual orientation. In a first instance, I address the issue of binarism and the crisis of identities in Western society. In a second instance, I analyse the linguistic complexities and epistemologies of non-binary gender; finally, I make a reading of the notion of gender through the hermeneutic perspective. To understand how the non-binary gender constitutes a dissidence from the hegemonic genders and offers a deconstructed conception and interpretation of language and therefore of the world.